A new staining protocol for detection of murine antibody‐secreting plasma cell subsets by flow cytometry. Issue 8 (13th July 2017) - Pracht, Katharina; Meinzinger, Julia; Daum, Patrick; Schulz, Sebastian R.; Reimer, Dorothea; Hauke, Manuela; Roth, Edith; Mielenz, Dirk; Berek, Claudia; Côrte‐Real, Joana; Jäck, Hans‐Martin; Schuh, Wolfgang
Abstract : We provide a robust four‐color fluorescence‐based flow cytometry protocol that distinguishes viable dividing plasmablasts from nondividing plasma cells and, based on CD19 surface abundance, identifies two mature plasma cell populations in the spleen and the bone marrow of mice.